The Occult in Modernist Art, Literature, and Cinema (Palgrave Studies in New Religions and Alternative Spiritualities, 2018)
Many modernist and avant-garde artists and authors were fascinated by the occult movements of their day. This volume explores how Occultism came to shape modernist art, literature, and film. Individual chapters examine the presence and role of Occultism in the work of such modernist luminaries as Rainer Maria Rilke, August Strindberg, W.B. Yeats, Joséphin Péladan and the artist Jan Švankmaier, as well as in avant-garde film, post-war Greek Surrealism, and Scandinavian Retrogardism. Combining the theoretical and methodological foundations of the field of Esotericism Studies with those of Literary Studies, Art History, and Cinema Studies, this volume provides in-depth and nuanced perspectives upon the relationship between Occultism and Modernism in the Western arts from the nineteenth century to the present day. .